-2x-1x=-2

Simple and best practice solution for -2x-1x=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-1x=-2 equation:


Simplifying
-2x + -1x = -2

Combine like terms: -2x + -1x = -3x
-3x = -2

Solving
-3x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-3'.
x = 0.6666666667

Simplifying
x = 0.6666666667

See similar equations:

| (2x^2+5-3)=0 | | g-500=225-g | | -(-10+4)+-(-40)= | | 3x^3+x^2-10=0 | | 3t-1=4t+16 | | .5r-.25=.5-.25r | | 2y^2-6y+8=0 | | 8z=2(4z+2) | | 3-2n=13+3n | | 69c-(27c-51)= | | 4+(d+2)-2d=3(2+d) | | 7a^3+b^4= | | r+10=7t-14 | | -12-(-12)-4+(-6)= | | 19+52y-11+7=62 | | 7m+49+4m=137 | | 2x^3-42x^2+252x-352=0 | | 1360*0.45= | | 90x-9x^2-100=0 | | 0+12=12 | | -(t+1)= | | 15-21=-n | | .45x=62.49 | | 5(12-2e)=20 | | -10-(-9)-5+(-3)= | | 19x+5y=8 | | 11(2x-2)+8=74 | | 6x-54=-12x+36 | | -(x-75)= | | 3(4x+9)=75 | | 5(n-10)-7n=18 | | 2x+64=180 |

Equations solver categories